Process and Delivery of Media Relations in Malaysia - Mohd Yahya Mohamed Ariffin; Md Sidin Ahmad Ishak (University of Malaya, 2024)
Media relations materials such as press release, notes-to-the-editor and invitations to the media have remained unrivalled tools in contemporary public relations. The use of such materials in marketing communication is relatively inexpensive, effective and has proven to be successful. In this research, a total of 420 materials relating to public relations were gathered from two media organizations, namely Berita Harian newspaper and the TV3 of Malaysia, to explore the common practices in preparing and disseminating public relations articles in the country. The research aims to analyze the sources and determine the predominant issues in the materials received by the selected media organizations. It also examines the extent to which common professional questions in news writing are observed in the articles. Findings show that the materials received by the two media organizations are from various categories of public and private organizations, and are dominated by social and economic issues in comparing to the other issues. Although, most of the materials analyzed indicated a need for improving the professional quality of the writing, they significantly satisfied the requirement for important information.